Changing the conventional university classroom - Blessinger, Patrick; Sengupta, Enakshi (Emerald Publishing Limited, 2022)
Changing the Conventional University Classroom highlights the interesting interventions practiced around the world by higher education instructors who were forced to make necessary changes in the conversion from face-to-face educational instruction to the use of online and virtual platforms owing to the COVID pandemic. Chronicling how academic staff and instructors were pushed to utilize modern technology and virtual exchange platforms to create meaningful classroom discussions and facilitate lively interactions between learners and faculty members, the chapters showcase the importance of quality assurance and reveal how educators prioritized regular monitoring of students' interaction, performance, and involvement in class. Collated in this collection of contemporary research, each chapter provides insight into the rapid evolution of educational approaches during the pandemic. Scholars demonstrate how these changes to the conventional way of teaching have shaped the field of education, and how technology is expected to bring further radical improvements in the near future.